Prevalencia De Anemia Ferropenica En Niños Menores De 10 Años Atendidos En El Centro De Salud Inkawasi - Lambayeque, Julio – Diciembre 2019 - Chavesta Nuñez, Pedro Jhonatan (2020)
The objective of this research work is to determine the prevalence of iron deficiency anemia in children from 0 to 10 years of age treated at the Inkawasi - Lambayeque Health Center, during July - December 2019. The study was descriptive, cross-sectional and correlational, consisting of 613 capillary blood samples from children from 0 to 10 years. Anemia was determined by measuring hemoglobin, using the method of microhematocrit and azidametahemoglobin (portable hemoglobinometer - Hemocue and microcuvettes), taking into account the values of the World Health Organization (WHO) and the adjustment of hemoglobin according to the altitude above sea level. The results obtained showed that 38.3% had iron deficiency anemia, 76.2% with mild anemia and 23.8% with moderate anemia; the female gender was the most affected with 52.3%, being the ages of 1 year with 29.8% and 2 years with 27.2% with greater prevalence, coming from Huasicaj with 20% and Inkawasi with 15.3%. The relationship of variables was analyzed, applying the Rho Spearman Correlation, obtaining: Prevalence - Age Group Ratio, a value of p = 0.01 <0.05, being a low and inversely proportional correlation for being negative; Relationship Prevalence - Type of Anemia, p value = 0.01 <0.05, with a very high positive correlation; Age Group Relationship - Type of Anemia, value of p = 0.01 <0.05, with a low and inversely proportional correlation for being negative